Legal Enforcement Challenges in Implementing Environmental Impact Assessment (AMDAL) Regulations in the Mining Sector in Kalimantan - Arifuddin, Muhammad Gaffar (Generasi Sains Indonesia, 2025)
This study examines the challenges of legal enforcement in implementing Environmental Impact Assessment (AMDAL) regulations within the mining sector in Kalimantan, Indonesia. Although AMDAL is designed as a key preventive legal instrument to integrate environmental considerations into development planning, its enforcement remains weak, inconsistent, and highly influenced by political interests. Using a qualitative socio-legal approach, this research draws on documentary analysis, semi-structured interviews with government officials, mining company representatives, and community members, as well as field observations conducted in East, Central, and South Kalimantan. The findings reveal three interrelated dimensions of enforcement failure. First, institutional fragility persists due to limited technical capacity, insufficient budgets, and fragmented coordination among environmental agencies. Second, selective enforcement practices emerge through corporate–political collusion, undermining the rule of law and reducing AMDAL to a procedural formality rather than a substantive safeguard. Third, community participation remains restricted, as local residents are often excluded from decision-making processes and lack access to environmental information. Collectively, these conditions transform AMDAL into a symbolic administrative requirement rather than an effective regulatory tool. The study concludes that strengthening institutions, insulating environmental governance from political interests, and empowering communities are essential to improving AMDAL enforcement and environmental protection in Indonesia’s extractive sectors.